2019
DOI: 10.1155/2019/9371790
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive and Efficient Method for Determination of Capecitabine and Its Five Metabolites in Human Plasma Based on One-Step Liquid-Liquid Extraction

Abstract: Colorectal cancer is the most common critical disease both in the developed and developing countries. Capecitabine, which has served in clinical practice at least for 10 years, is a first-line antidigestive tract cancer drug for its better efficacy, patient compliance, and lower side effects. An ultra-high-performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) method has been developed and completely validated for simultaneous determination of capecitabine and its five metabolites in human pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…A clear drawback of this method is that an extra step is introduced which complicates the sample pretreatment and prolongs the duration of sample pretreatment (Licea‐Perez et al, ). Wang et al () reported that they tested several separation methods (SPE and PP) and extraction fluids, but that the use of a one‐step liquid‐liquid extraction of capecitabine, 5‐‘dFCR, 5’‐dFUR, 5‐fluoro‐2’‐deoxyuridine (FdUrd), 5‐FU and 5‐FUH 2 by ethyl acetate and isopropanol (19:1, v/v) gave optimal extraction recovery (59.3% to 90.2%) (Wang et al, ).…”
Section: Sample Pre‐treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…A clear drawback of this method is that an extra step is introduced which complicates the sample pretreatment and prolongs the duration of sample pretreatment (Licea‐Perez et al, ). Wang et al () reported that they tested several separation methods (SPE and PP) and extraction fluids, but that the use of a one‐step liquid‐liquid extraction of capecitabine, 5‐‘dFCR, 5’‐dFUR, 5‐fluoro‐2’‐deoxyuridine (FdUrd), 5‐FU and 5‐FUH 2 by ethyl acetate and isopropanol (19:1, v/v) gave optimal extraction recovery (59.3% to 90.2%) (Wang et al, ).…”
Section: Sample Pre‐treatmentmentioning
confidence: 99%
“…This was shown by Wang et al . whom have tested both LLE and PP and reported that LLE could remove interfering endogenous components at the greatest extent and subsequently showed less of a matrix effect compared to PP (Wang et al, ). Nevertheless, PP can still be an excellent option for sample pre‐treatment of capecitabine and its metabolites.…”
Section: Sample Pre‐treatmentmentioning
confidence: 99%
See 3 more Smart Citations